Feasibility of personalised remote long-term follow-up of people with cochlear implants: a randomised controlled trial - Cullington, Helen; Kitterick, Pádraig T.; Weal, Mark; Margol-Gromada, Magdalena (BMJ Publishing Group Ltd., 2018)
Introduction: substantial resources are required to provide lifelong post-operative care to people with cochlear implants. Most patients visit the clinic annually. We introduced a person-centred remote follow-up pathway, giving patients telemedicine tools to use at home so they would only visit the centre when intervention was required. Objectives: to assess the feasibility of comparing a remote care pathway to the standard pathway in adults using cochlear implants. Design: two-arm Randomised Controlled Trial. Randomisation used a minimisation approach, controlling for potential confounding factors. Participant blinding was not possible, but baseline measures occurred before allocation. Setting: University of Southampton Auditory Implant Service: provider of NHS care. Participants: 60 adults who had used cochlear implants for at least 6 months. Interventions: control group (n = 30) followed usual care pathway. Remote care group (n = 30) received care remotely for 6 months incorporating: •Home hearing in noise test •Online support tool •Self-adjustment of device (only 10 had compatible equipment) Main outcome measures: Primary: change in patient activation; measured using the Patient Activation Measure® Secondary: change in hearing and quality of life; qualitative feedback from patients and clinicians. Results: one participant in the remote care group dropped out. The remote care group showed a greater increase in patient activation than the control group. Changes in hearing differed between the groups. The remote care group improved on the Triple Digit Test hearing test; the control group perceived their hearing was worse on the Speech, Spatial and Qualities of Hearing questionnaire. Quality of life remained unchanged in both groups. Patients and clinicians were generally positive about remote care tools and wanted to continue. Conclusions: adults with cochlear implants were willing to be randomised and complied with the protocol. Personalised remote care for long-term follow-up is feasible and acceptable, leading to more empowered patients.